Chain length-dependent mitochondrial toxicity of perfluoroalkyl carboxylic acids: insights from Mito Tox Index evaluation - Kam, Yoonseok; Winer, Lisa; Romero, Natalia (Frontiers in Toxicology, 2025)
IntroductionPer- and polyfluoroalkyl substances (PFAS) are persistent environmental contaminants that accumulate in living organisms, posing significant human health risks. The toxicity mechanisms of PFAS include mitochondrial dysfunction and bioenergetic failure.MethodsThis study evaluates the structure-activity relationship of PFAS compounds with mitochondrial toxicity by comparing the Mito Tox Index (MTI) of perfluoroalkyl carboxylic acids (PFCAs) varying carbon chain lengths. The MTI quantifies the extent to which substances disrupt mitochondrial function by distinguishing between mitochondrial inhibition and uncoupling. This was followed by an assessment of the effect of PFCAs on total cellular bioenergetics and impedance-based real time cell viability measurement.Results and discussionBoth inhibition and uncoupling MTI values increased with the chain length of PFCAs and severe mitochondrial inhibition was observed when uncoupling was maximized by PFCAs containing seven or more carbons within hours of exposure. The mitochondrial toxicity corresponded well to the bioenergetic failure measured by real-time ATP production rates. In contrast, there was a substantial difference between cytotoxicity and mitochondrial toxicity, despite a common trend of increased toxicity with longer chain lengths. The results suggest that PFCA-induced mitochondrial dysfunction is a key mechanism of PFAS-mediated cellular damage, primarily driven by proton leak-mediated ETC uncoupling, leading to impaired mitochondrial energy production. It also implies that MTI-based mitochondrial toxicity evaluation increases data precision in comparing PFAS effects on mitochondrial function, even identifying the mode of action, which is expected to improve in vitro toxicity prediction models.